Directions for a National Manpower Policy A Report on the Proceedings of Three Regional Conferences. Special Report No. 13. - National Commission for Manpower Policy, Washington, DC.; National Commission for Manpower Policy, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
The three conference reports summarized were prepared by the sponsors of the Regional (eastern, central, and western) Conferences on Directions for a National Manpower Policy held in September and October 1976. Each of these summaries is a separate section consisting of a summary of the conference proceedings, a summary of the speeches and papers presented at the conference, any comments submitted by conference participants, a list of the discussion questions used at the conference, and a list of the conference participants. Each of the summaries focuses on the same broad themes--Employment Problems of Youth: Improving the Transition from School to Work; Manpower Programs and Services: Infrastructure and Delivery; and Issues and Elements in the Design of a National Manpower Policy. (WL)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Conference Reports; Delivery Systems; Employment Problems; Government Role; Labor Force Development; National Programs; Policy Formation; Program Development; Regional Planning; Unemployment; Vocational Adjustment; Vocational Education; Youth Employment; United States; Collected Works, Proceedings